Hcp and VgrG1 are secreted components of the Helicobacter hepaticus type VI secretion system and VgrG1 increases the bacterial colitogenic potential. (17th January 2013) - Bartonickova, Lucie; Sterzenbach, Torsten; Nell, Sandra; Kops, Friederike; Schulze, Jessika; Venzke, Annika; Brenneke, Birgit; Bader, Sophie; Gruber, Achim D.; Suerbaum, Sebastian; Josenhans, Christine
Summary The enterohepatic Epsilonproteobacterium Helicobacter hepaticus persistently colonizes the intestine of mice and causes chronic inflammatory symptoms in susceptible mouse strains. The bacterial factors causing intestinal inflammation are poorly characterized. A large genomic pathogenicity island, HHGI1, which encodes components of a type VI secretion system (T6SS), was previously shown to contribute to the colitogenic potential of H. hepaticus. We have now characterized the T6SS components Hcp, VgrG1, VgrG2 and VgrG3, encoded on HHGI1, including the potential impact of the T6SS on intestinal inflammation in a mouse T‐cell transfer model. The H. hepaticus T6SS components were expressed during the infection and secreted in a T6SS‐dependent manner, when the bacteria were cultured either in the presence or in the absence of mouse intestinal epithelial cells. Mutants deficient in VgrG1 displayed a significantly lower colitogenic potential in T‐cell‐transferred C57BL/6 Rag2−/− mice, despite an unaltered ability to colonize mice persistently. Intestinal microbiota analyses demonstrated only minor changes in mice infected with wild‐typeH. hepaticus as compared with mice infected with VgrG1‐deficient isogenic bacteria. In addition, competitive assays between both wild‐type and T6SS‐deficient H. hepaticus, and between wild‐type H. hepaticus and Campylobacter jejuni or Enterobacteriaceae species did not show an effect of the T6SS on interbacterial competitiveness. Therefore, we suggest that microbiota alterations did not play a major role in the changes of pro‐inflammatory potential mediated by the T6SS. Cellular innate pro‐inflammatory responses were increased by the secreted T6SS proteins VgrG1 and VgrG2. We therefore concluded that the type VI secretion component VgrG1 can modulate and specifically exacerbate the innate pro‐inflammatory effect of the chronic H. hepaticus infection.